The Florida Mobile Health Adherence Project for People Living With HIV (FL-mAPP): Longitudinal Assessment of Feasibility, Acceptability, and Clinical Outcomes - Escobar-Viera, César; Zhou, Zhi; Morano, Jamie P; Lucero, Robert; Lieb, Spencer; McIntosh, Sean; Clauson, Kevin A; Cook, Robert L (JMIR Publications, 2020)
BackgroundFor people living with HIV (PLWH), antiretroviral therapy (ART) adherence is crucial to attain better health outcomes. Although research has leveraged consumer health information technologies to enhance ART adherence, no study has evaluated feasibility and clinical outcomes associated with the usage of a commercially available, regularly updated mobile health (mHealth) app for improving ART adherence among PLWH. ObjectiveThis study aimed to assess the feasibility, acceptability, and clinical outcomes of Care4Today, an existing, free, biprogrammatic mHealth app for improving ART adherence among PLWH. MethodsThe Florida mHealth Application Adherence Project (FL-mAPP) was a 90-day longitudinal pilot study conducted in 3 public HIV clinics in Florida, United States. After obtaining informed consent, 132 participants completed a survey and then were given the option to try an existing mHealth app to help with ART adherence. Of these, 33.3% (44/132) declined, 31.1% (41/132) agreed but never used the app, and 35.6% (47/132) used the app. All were asked to complete follow-up surveys at 30 days and 90 days after enrollment. Usage data were used to assess feasibility. Clinical outcomes of self-reported ART adherence and chart-obtained HIV viral load and CD4+ T-cell counts were compared among those who used the platform (users) versus those who did not (nonusers). Participants and HIV care providers also provided responses to open-ended questions about what they liked and did not like about the app; comments were analyzed using thematic analysis. ResultsOf 132 participants, 47 (35.6%) and 85 (64.4%) were categorized as users and nonusers, respectively. Among users, a Kaplan-Meier plot showed that 25 persons (53%) continued using the app after the 90-day follow-up. At 30-day follow-up, 13 (81.3%) of those who used the mHealth app reported ≥95% ART adherence, compared with 17 (58.6%) nonusers (P=.12). Overall, 39 (82%) users liked or somewhat liked using the platform. Participants' favorite features were medication reminders, ability to create custom reminders, and adherence reports. ConclusionsThis longitudinal study found that a commercially available medication adherence mHealth app was a feasible and acceptable intervention to improve ART adherence among PLWH and engaged in clinical care across 3 public HIV clinics in the state of Florida. Overall, participants liked the Care4Today app and thought the medication reminders were their favorite feature. Generally, self-reports of ART adherence were better among users than nonusers, both at 30- and 90-day follow-ups. Further clinical research needs to address user fatigue for improving app usage.